Two new species in the leafhopper genus Pythamus Melichar (Hemiptera: Cicadellidae: Evacanthinae) from China - Wang, Yang; Zhang, Yalin (Zootaxa, 2015)
Two new leafhopper species, Pythamus hainanensis sp. nov. and Pythamus rufus sp. nov. from China, are described and illustrated. Their diagnostic characteristics are compared with similar species. One new combination, Riseveinus chiabaotawow (Huang, 1992) n. comb., is also proposed. In addition, P. biramosus and P. bispinosus are illustrated based on paratypes. A key to known species of Pythamus is provided, excluding three species for which placement cannot presently be confirmed.